Pengaruh Akurasi Gambar Teknik Digital Terhadap Efisiensi Sumber Daya Dan Mitigasi Risiko Kecelakaan Di Lingkungan Manufaktur - Maslikhan Maslikhan; Muhammad Waqar Mazhar (Ekliptika, 2026)
Inaccurate engineering drawings directly impact material waste and safety risks in factories. This article analyzes the comparison of manual and digital methods (SketchUp) in achieving industrial precision standards and their relationship to Sustainable Development Goals (SDGs) 9 and 12. Using a descriptive quantitative approach, the study identified barriers to learning digital technology among engineering students. The results showed that the average barrier index reached 62.5% (High Category), with the main obstacles being industrial relevance and hardware limitations. Nevertheless, the integration of 3D visualization proved crucial in improving spatial understanding to prevent workplace accidents and support Green Manufacturing. The integration of intensive practical training is recommended to ensure energy-efficient and operationally safe product quality.